(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim. The purpose of this study was to assess and compare the dimensional accuracies of five brands of extended pour irreversible hydrocolloid materials for fixed dental prosthesis impression. Materials and methods. Impressions of a master stainless steel model were made with five extended pour irreversible hydrocolloids and one addition silicone impression material. A total of ninety impressions (n=90) were made, with fifteen for each group of impression material. The stone dies retrieved from these impressions were analysed with Baty-Vision Systems - Venture 3D CNC machine, for dimensional accuracies. Comparison of continuous data between two groups was done with the Wilcoxon rank-sum test (Mann Whitney U test) and for more than two groups with the Kruskal Wallis test (? = .05) Results. All six impression materials showed some amount of error. On comparison of the median total absolute deviation of the various dimension of stone dies, the accuracies of impression materials in decreasing order appeared to be Neocolloid >> Affinis >> Coltoprint >> Zelgan >> 3M ESPE >> Plastalgin. On the contrary, a comparison of the impression materials, in terms of several dimensions of stone dies differing significantly from the stainless-steel model, the sequence in terms of accuracy was, Coltoprint > Affinis >3M ESPE > Neocolloid > Plastalgin > Zelgan. Conclusions. Based on the dimensional accuracies of the stone dies retrieved from the impressions, Neocolloid was found to be the best impression material with the least possible deviation, followed by Coltoprint and Affinis.